SURGICAL MANAGEMENT OF A RARE CASE OF QUADRUPLETS IN A DOE COMPRISING OF DUAL MUMMIES, A STILLBORN AND A LIVE KID - M. Praveen Kumar; B. Chandra Prasad; M. Srinivas (Indian Journal of Veterinary and Animal Sciences Research, 2025)
A pluriparous non-descript doe was presented with the history of dystocia. Clinical investigation revealed the presence of closed cervix and lodged multiple foetuses in the tract. Laparo-hysterotomy was performed and four foetuses were relieved, of which one was alive, one was still born and the other two were mummified. Thus the present report describes the incidence of quadruplets in a doe comprising of dual mummies along with a stillborn and a live kid.